ANALISIS PENGARUH CORPORATE GOVERNANCE TERHADAP AUDIT REPORT LAG - Pinayungan, Iunike Karyasari; Basuki Hadiprajitno, Paulus Th (Diponegoro Journal of Accounting, 2019)
The aims of this study is to examine the effect of characteristic corporate governance, such as ownership concentration, independent board of commissioners, CEO tenure, audit committee size and number of audit committee meetings on audit report lag. This study uses company size, type of auditor and profitability as control variables.The population of this study are manufacturing companies listed on the Indonesia Stock Exchange in 2015, 2016, and 2017. Based on the purposive sampling method, there are 79 companies that met the sampling criteria. Data analyzed with test of classic assumption and examination of hypothesis with multiple linear regression method. Result of this research indicates that number of audit committee meetings has negative significant effect on audit report lag, meanwhile , independent board of commissioners has positive significant effect on audit report lag. But on the other hand, ownership concentration, CEO tenure and audit committee size has insignificant effect on audit report lag.